Solid Waste Management (SWM) Conditions, Practices, and Challenges of Select Barangays in Lipa City - Joan Villanueva; Annabelle Magsino; Floryfe Hernandez; Abigail Marie Hernandez (Philippine Association of Institutions for Research, Inc., 2021)
One of the significant challenges around the globe is solid waste and solid waste management. In Lipa City alone, over 167kilos of garbage are produced per day, making it the second biggest waste generator in Batangas province. The study aimed to identify the city's solid waste management conditions, practices, and challenges, focusing on three selected barangays. The focus was to identify, evaluate, assess the existing solid waste management; and design and develop a piece of equipment as an alternative way ideal for the current condition of solid waste management for these barangays in Lipa City. This study used the descriptive-evaluative and quantitative research design; utilized the 10-year Ecological Solid Waste Management Plan of the Lipa City Environmental and Natural Resources Office or CENRO; and a personal interview with the head and 27 staff in the solid waste management of the city. This study found out that problems still arise despite the strict implementation of solid waste management in these three barangays. As part of the program to be implemented, the researchers proposed introducing a biodegradable composter known as BIOCOM.